Analysis Of The Implementation Of The Official Manuscript System For Employees At The Regional Office V Of The State Civil Service Agency Jakarta - Fauzia, Marcellia; Marsofiyati; Christian Wiradendi Wolor, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The research made uses a qualitative descriptive approach, namely by describing and analyzing all the problems found in the field. Qualitative research is based on primary and secondary data. Primary data in this study was obtained by means of observation, interviews, and documentation, while secondary data was obtained through reading sources such as books, previous research, and articles related to the research topic in this study. The purpose of this study was to determine the application of the employee service script system which includes procedures for implementing the employee service script system, storing the employee service script system and obstacles and solutions in implementing the employee service script system. From the results of the study, it can be seen that the Regional Office V of the Jakarta State Civil Service Agency has implemented a good employee official script system, but there needs to be an improvement regarding the system used so that the implementation of the employee script system can be used to optimize employee performance in work operations.